PERAN SPIRITUALITAS DENGAN KESADARAN EMOSI DAN COPING REMAJA - Alif Muarifah; Ahmad Muhammad Diponegoro; Rohmatus Naini; Siti Partini Suadirman; Tasya Amin Zakiyah; Diki Herdiansyah (State Islamic University (UIN) Salatiga, 2024)
Adolescence is a period that has a very unique development. Spirituality is core to the individual's process of becoming holistically healthy. This study aims to determine the relationship between spirituality, emotional awareness, and coping among adolescents in Yogyakarta. The research method used was correlational with a direct survey of 525 students aged 14-18 years at the high school level. The research instrument used was the Wellness Evaluation of Lifestyle inventory, which Naini (2013) adopted through back translation and adaptation to the Indonesian language and culture. The data analysis technique used is Pearson correlation. The research results show spirituality with emotional awareness and coping with a Pearson correlation of .325 and p = .000 (p<.05). This study concludes that there is a relationship between spirituality, emotional awareness, and coping in adolescents.